The Effect of the Housing System, Season and the Linseed Oil Ethyl Esters Additive on Selected Blood Parameters in Rabbits - Katarzyna Roman; Martyna Wilk; Piotr Książek; Katarzyna Czyż; Adam Roman (Animals, 2022)
The composition of the diet, including the amount and type of lipid supplements, influences the products formed in the digestive tract, their levels in the blood and their deposition in the tissues. One example of a plant rich in polyunsaturated fatty acids is flax (Linum usitatissimum). The aim of the presented work was to evaluate the effect of the linseed oil ethyl esters additive and environmental conditions on the selected rabbit blood parameters. The study included two types of animal maintenance (laboratory conditions and external conditions) and two seasons (summer and winter), a total of four study stages. At each stage, a control group and an experimental group were specified. The feed supplement in the form of esterified linseed oil was administered to the experimental animals for two months. The blood samples were collected at the beginning of the experiment, as well as at the end of treatment. Moreover, blood samples were collected also after two months from the end of the experiment. During the experiment, morphological and biochemical parameters of the rabbits’ blood were examined. The results of the content of fatty acids were determined in the erythrocytes and serum blood samples and grouped into saturated and unsaturated fatty acids, especially omega-3 and omega-6 fatty acids. In an internal study, the influence of housing conditions and season on selected morphological and biochemical parameters of rabbit blood was confirmed. Furthermore, expected beneficial changes in the fatty acid profile in erythrocytes and blood serum were observed as a result of supplementation. A significant increase in omega-3 fatty acids was noted as well as a substantial decrease in the ratio of omega-6 to omega-3 fatty acids (p < 0.01). Most importantly, the linseed oil ethyl ester supplement used did not adversely affect the health of the rabbits, as evidenced by biochemical and blood morphological indices remaining within, known so far, reference limits or showing only slight fluctuations (p > 0.05). However, the obtained results extend the database of hematological blood parameters in rabbits, thus, contributing to improvements in laboratory diagnostics for fur animals.